2020
DOI: 10.3892/mmr.2020.11087
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel USH2A mutations in patients with autosomal recessive retinitis pigmentosa via targeted next‑generation sequencing

Abstract: retinitis pigmentosa (rP) is a group of inheritable blindness retinal diseases characterized by the death of photoreceptor cells and a gradual loss of peripheral vision. Mutations in usher syndrome type 2 (USH2A) have been reported in rP with or without hearing loss. The present study aimed to identify causative mutations in a cohort of families with rP from china. a cohort of 62 non-syndromic families with rP and 30 sporadic cases were enrolled in this study. all affected members underwent a complete ophthalm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Studies of two newly identified USH2A variants in two Korean families have demonstrated more profound and progressive hearing loss than expected for USH2, requiring cochlear implantation . Furthermore, some USH2A associated genotypes show variable expressivity, with phenotypic variance seen both interfamilial and intrafamilial (Liu et al 1999;Bernal et al 2005;Austin-Tse et al 2018;Qu et al 2020;Zhu et al 2020).…”
Section: Usher Syndrome Type IImentioning
confidence: 99%
“…Studies of two newly identified USH2A variants in two Korean families have demonstrated more profound and progressive hearing loss than expected for USH2, requiring cochlear implantation . Furthermore, some USH2A associated genotypes show variable expressivity, with phenotypic variance seen both interfamilial and intrafamilial (Liu et al 1999;Bernal et al 2005;Austin-Tse et al 2018;Qu et al 2020;Zhu et al 2020).…”
Section: Usher Syndrome Type IImentioning
confidence: 99%
“…The association between the va r iations in usher syndrome-causative genes and the resultant usher syndrome diseases or phenotypes in patients are highly variable; the genotype/phenotype associations are also divergent (1,3,4). Since eudy et al (5) first identified three mutations in the USH2A gene in patients with usher syndrome type iia with rP and hearing loss, additional USH2A mutations have been shown to be associated with usher syndrome type IIA (10)(11)(12)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Since Eudy et al ( 5 ) first identified three mutations in the USH2A gene in patients with Usher syndrome type IIA with RP and hearing loss, additional USH2A mutations have been shown to be associated with Usher syndrome type IIA ( 10 12 , 32 39 ). Patients with autosomal recessive RP (arRP; RP39; OMIM, 613809) without hearing loss were also identified to possess USH2A mutations, highlighting the complexity of genotype/phenotype associations in this disease ( 4 ). For example, Rivolta et al ( 40 ) identified USH2A mutations in patients with arRP without hearing loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, identifying novel disease genes or variants is important to increase the diagnostic rate and to facilitate new approaches for clinical care of IRD patients. The advances in next-generation sequencing (NGS) technologies have ushered in a new era for genetic diagnosis and disease-gene discovery 7 . Recent studies have reported the clinical utility of Whole Genome Sequencing (WGS), especially for rare diseases 8 , 9 , and its large expectations on personalized medicine 10 , highlighting that the use of WGS as a first diagnostic strategy could constitute a unique and powerful analysis.…”
Section: Introductionmentioning
confidence: 99%